Protective effect of phage pSal-4 on chicken intestinal epithelial cells injured by Salmonella enteritidis - Ziqiang Xie; Xingbang Lv; Cuihong Zhong; Fangfang Wang; Yongying Zhang; Yue Li; Yangling Huang; Shuo Yang; Yuxiang Shi (BMC Microbiology)
Abstract Salmonella enteritidis plays a significant role in zoonotic infections. This pathogen settles in the intestinal tract of poultry and contaminates meat and egg products during production for slaughter. Consequently, it can also be transmitted to humans along the food chain, posing a significant risk to public health. Bacteriophages offer a viable substitute for antibiotics in treating Salmonella enteritidis due to their specific bactericidal effect and safety. This study aimed to investigate the protective effect of bacteriophage against Salmonella enteritidis infection in chicken intestinal epithelial cells. Chicken intestinal epithelial cells were treated with various concentrations of bacterial suspension, and the impact on cell damage was assessed by measuring changes in cell viability and observing structural changes via transmission electron microscopy. In the phage protection experiment, the phages were co-incubated with Salmonella enteritidis for 2, 4, and 6 h. Thereafter, the adhesion rate and invasion rate of bacteria and gene transcription levels of Occludin, Claudin-1, ZO-1, NF-κB p65, TNF-α and IL-6 in cells were determined. The results indicated that the phage could significantly reduce both adhesion and invasion rates of Salmonella enteritidis at MOI = 10 (P < 0.05). Following phage treatment of the co-culture of chicken intestinal epithelial cells and Salmonella enteritidis (CICC10467), there was a significant reduction in the gene expression of pro-inflammatory cytokines NF-κB p65, TNF-α and IL-6, and a significant increase in the gene expression of anti-inflammatory cytokines Occludin, Claudin-1, and ZO-1. This indicates that the phage can inhibit the infection of chicken small intestinal epithelial cells by Salmonella enteritidis. Furthermore, phages were able to significantly alleviate inflammation and barrier integrity disruption caused by the bacteria in the co-culture. These observations suggest that phages are promising candidates for preventing and treating gastrointestinal bacterial infections.